Transparency in Complex Compensation Systems - Ana Möller Quintanar (Junior Management Science (JUMS), 2022)
The purpose of the present work is to examine the effects of full pay transparency, in the organisational context of complex compensation systems, on the comparisons employees draw between each other. To do so, an overview of compensation systems, including their purposes and components is presented. Second, the term of full pay transparency is introduced and defined. Lastly, this work offers several scenarios of social comparisons conducted under full pay openness in an equitable compensation system. In a first scenario, where employees pose as fully rational actors, full pay transparency presents positive fairness perceptions of the pay structure. In a second scenario, in which organisational members' rationality is inhibited by biases, the compensation system is perceived as inequitable, other things equal. Concluding, full pay openness does not necessarily garner positive effects in social comparisons. Furthermore, variable pay, as a component of the pay mix, seems to pose a hindrance to the fairness perceptions of employees. The author notes that an adequate communication strategy and involvement of employees in the strategic process of implementing full pay transparency may counter the negative effects found.
Keywords: 650; Compensation; pay transparency; social comparison